Proceedings of the 2021 CHI Conference on Human Factors in Computing Systems 2021
DOI: 10.1145/3411764.3445318
|View full text |Cite
|
Sign up to set email alerts
|

When the Social Becomes Non-Human: Young People's Perception of Social Support in Chatbots

Abstract: Although social support is important for health and well-being, many young people are hesitant to reach out for support. The emerging uptake of chatbots for social and emotional purposes entails opportunities and concerns regarding non-human agents as sources of social support. To explore this, we invited 16 participants (16-21 years) to use and refect on chatbots as sources of social support. Our participants frst interacted with a chatbot for mental health (Woebot) for two weeks. Next, they participated in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 71 publications
3
25
0
Order By: Relevance
“…First, the data in this study are limited to users who accessed and used a particular chatbot. Given that the primary user group of the chatbot service studied is young adults [ 4 ], our findings may not be generalizable to other populations and age groups. Our study also focused on a particular social chatbot, and its findings might not be generalizable to other types of conversational agents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, the data in this study are limited to users who accessed and used a particular chatbot. Given that the primary user group of the chatbot service studied is young adults [ 4 ], our findings may not be generalizable to other populations and age groups. Our study also focused on a particular social chatbot, and its findings might not be generalizable to other types of conversational agents.…”
Section: Discussionmentioning
confidence: 99%
“…Chatbots are an emerging digital platform that has received considerable attention from public health initiatives during the novel coronavirus (COVID-19) pandemic [ 3 ]. Chatbots are systems that interact with users via text or voice and use natural language [ 4 ]. They have been widely used for amusement (eg, small talk) and business (eg, customer service and sales) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be done using clinical interviews supplementing self-reporting data for the same type of empirical development. Previous research has showed that adolescents appreciate support from conversational agents such as Woebot [ 63 ]. However, the field of adolescent mental health is complex and involves different life areas such as school, social life, parents, and family.…”
Section: Discussionmentioning
confidence: 99%
“…Bae Brandtzæg et al. (2021) designed a chatbot to support young people with sex, school, bullying, feelings, love, and divorce issues. They found that users perceived social support from the chatbot and that it was easier to self‐disclose to a chatbot than to a human because chatbots provide anonymity and privacy.…”
Section: Introductionmentioning
confidence: 99%